Rupture analysis of a road embankment built on soft soil in the city of Goiana-PE, Brazil (Research, Society and Development, 2022)
Soft soil deposits are known for having high compressibility and low values of hydraulic conductivity and shear strength. During the duplication roadwork of BR-101, a 4 km stretch of was built on the soft soil of the lowland of Goiana-PE, Brazil. The embankment segment under study is located between the piles 3474 and 3490, with a length of 320 meters. This paper aims to analyze field and laboratory tests, as well as understand the failure of a embankment on soft soil through very well known stability control methods. Standard penetration test (SPT), Vane shear test and undisturbed soil sampling collection were conducted in situ while in the laboratory, soil classification, standard index, standard oedometric and triaxial (UU) tests were performed. The geological-geotechnical profile shows a superficial layer of silty clay (2.8 meters), followed by a thick layer of very soft silty clay with organic content (14.0 meters). Undisturbed samples were classified as very poor, with medium sensitivity. The undrained shear strengths obtained by triaxial tests (UU) are close to those obtained by vane shear tests. The inclinometer evidenced significant values of horizontal displacement, enough to cause the instability of the area (rupture). Therefore, the poor sampling quality, misleading interpretation of the results and lack of clarity and objective may have favored the rupture of the embankment.